Anti-Obesity Effects of Marine Macroalgae Extract Caulerpa lentillifera in a Caenorhabditis elegans Model - Kawita Chumphoochai; Preeyanuch Manohong; Nakorn Niamnont; Montakan Tamtin; Prasert Sobhon; Krai Meemon (Marine Drugs, 2023)
Obesity is a multifactorial disease characterized by an excessive accumulation of fat, which in turn poses a significant risk to health. Bioactive compounds obtained from macroalgae have demonstrated their efficacy in combating obesity in various animal models. The green macroalgae Caulerpa lentillifera (CL) contains numerous active constituents. Hence, in the present study, we aimed to elucidate the beneficial anti-obesity effects of extracts derived from C. lentillifera using a Caenorhabditis elegans obesity model. The ethanol (CLET) and ethyl acetate (CLEA) extracts caused a significant decrease in fat consumption, reaching up to approximately 50–60%. Triglyceride levels in 50 mM glucose-fed worms were significantly reduced by approximately 200%. The GFP-labeled dhs-3, a marker for lipid droplets, exhibited a significant reduction in its level to approximately 30%. Furthermore, the level of intracellular ROS displayed a significant decrease of 18.26 to 23.91% in high-glucose-fed worms treated with CL extracts, while their lifespan remained unchanged. Additionally, the mRNA expression of genes associated with lipogenesis, such as sbp-1, showed a significant down-regulation following treatment with CL extracts. This finding was supported by a significant decrease (at 16.22–18.29%) in GFP-labeled sbp-1 gene expression. These results suggest that C. lentillifera extracts may facilitate a reduction in total fat accumulation induced by glucose through sbp-1 pathways. In summary, this study highlights the anti-obesity potential of compounds derived from C. lentillifera extracts in a C. elegans model of obesity, mediated by the suppression of lipogenesis pathways.